On Lyubeznik type invariants - Reichelt, Thomas; Walther, Uli; Zhang, Wenliang (Topology and its applications, 2022)
We discuss for an affine variety Y embedded in affine space X two sets of integers attached to Y⊆X via local and de Rham cohomology spectral sequences. We investigate collapse of the spectral sequences, give topological interpretations, study them in small dimension, and consider to what extent one can attach them to projective varieties.
Gesehen am 18.07.2022